Pengelolaan Daya Tarik Wisata Desa Alamendah, Kabupaten Bandung - Dwi Agiyanti; Devina Nur Hafizah (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This article aims to analyze and identify the quality of tourist attraction of Alamendah village and its application to the management of tourist attraction in Alamendah village, Rancabali District, Bandung Regency. The theory used in this study is the theory of tourism. Tourism is a trip made by a person or group from one place to another, temporary, this tourism aims as recreation, pleasure in seeking environmental balance in social, cultural, natural and scientific dimensions. Through survey and observation methods analyzing Alamendah tourism, this study collects data on tourists' perceptions of the tourist experience, quality of service, quality of physical tourism products, and sustainability of the attraction. Research findings show that a satisfactory travel experience is a key factor in determining the quality of Alamendah's tourist attraction. The results showed that the potential strategy of tourism villages that become tourist attractions, the types of tourism in Alamendah Village, factors that influence the increase in tourist visits to Alamendah Tourism Village such as glamping activity tour packages, tours and sports tourism as well as plantation tourism and digital tourism development strategies can increase tourist visits to Alamendah Tourism Village, The role of tourists in the development of Alamendah Village